ЕЛЕКТРОРОЗРЯДНІ ТЕХНОЛОГІЇ ОБРОБКИ ВОДИ ТА КРИТЕРІЇ ДОЦІЛЬНОСТІ ЇХНЬОГО ВИКОРИСТАННЯ - Берека, В.О.; Кондратенко, І.П. (Інститут електродинаміки Національної академії наук України, 2021)
The analysis of the known results of processing model aqueous solutions with different types of electric discharge using the AOT technology is carried out. Comparison of the processing efficiency for the decomposition of model pollutants for energy yield criterion (Y), as well as the prospects for further industrial implementation of the technology for the criterion of expected productivity, is carried out. The factors that influence the value of energy output and energy efficiency, in general, are determined. Ref. 17, fig. 2, tables 2.